Comparison of outpatient versus inpatient transurethral prostate resection for benign prostatic hyperplasia: Comparative, prospective bi-center study. - Park, Jae Young; Shim, Ji Sung; Lee, Jeong Gu; Moon, Du Geon; Yoo, Jeong woo; Choi, Hoon; Bae, Jae Hyun (Canadian Urological Association Journal, 2014)
Introduction: We compare the symptomatic relief with urodynamic parameter change and operative safety of the outpatient transurethral resection in saline (TURIS-V) technique with inpatient transurethral resection of the prostate (TURP) for the management of benign prostatic hyperplasia (BPH). Methods: This prospective cohort comparison study enrolled patients who needed BPH surgery. Between January 2010 and June 2011, outpatient TURIS-V was performed at 1 centre and the results of the treatment were compared with inpatient TURP performed at a separate hospital. Preoperative characteristics, including prostate volume, were similar in both groups. Perioperative data and any treatment complications were recorded. The analysis compared postoperative outcomes, including a 6-month postoperative International Prostate Symptom Score (IPSS), a quality of life (QoL) evaluation and a record of any changes in uroflowmetry findings, between the 2 groups. Results: In the TURIS-V patient group, 75 patients agreed to be in the study. Of these, 69 ultimately complete the study. In the TURP group, 76 patients agreed and 71 of these completed the study. Both study groups were well-matched for age, IPSS, QoL and uroflowmetry findings. The TURIS-V group experienced both shorter operation times (54.6 vs. 74.8 minutes) and shorter catheterization times (2.2 vs. 4.2 days) when compared to the TURP group. There were comparable improvements in the 6-month postoperative IPSS, QoL, and uroflowmetry findings between the 2 groups. There were also equally low incidence rates of procedural complications. Conclusions: Both TURIS-V and TURP relieve lower urinary tract symptoms in a similar way, with great efficacy and safety. Overall, TURIS-V had shorter operative and catheterization times compared to TURP. Notwithstanding the paper’s limitations (non- randomized cohort comparison with possible selection or surgeon bias and small heterogeneous sample size), TURIS-V can be performed safely even in an outpatient setting.